Penerapan Aplikasi Google classroom pada Proses Pembelajaran Dasar Listrik dan Elektronika di Sekolah Menengah Kejuruan - Azfar Hadi Rama Yasmen; Hastuti Hastuti (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to determine the impact of implementing the Google classroom application as a learning medium during the COVID-19 period for Basic Electrical and Electronics (DLE) subjects at SMK Muhammadiyah 1 Padang. The decrease in student activity when studying in the implementation of physical distance due to the COVID-19 outbreak and difficulties in understanding material and learning through WhatsApp because students are considered to be full of symbols or formulas that are systematic, so it is necessary to apply Online Media to the fullest. The method in this research is pre-experimental, using a research design of One Group Pretest-Posttest. The research subjects were students of class X TITL who opened 27 people. The sampling technique uses saturated sampling in a relatively small population (less than 30 people) with data collection techniques using pretest and posttest evaluations. Data analysis is Inferential Statistics to determine the effect of implementing the Google classroom application. The results showed that there was an increase in student learning in the experimental class which was known through the learning outcomes obtained that the average score (posttest) was positively increased compared to (pretest). These results conclude that the application of the Google classroom application is appropriate to be applied to students as a medium for learning Basic Electricity and Electronics during the COVID-19 period at SMK Muhammadiyah 1 Padang.